A Qualitative Study on Chemical Waste Management in Offset Printing and Its Impact on the Surrounding Environment - Juwairiah (SERUNAI, 2025)
ABSTRACT This study aims to explore the practices of chemical waste management in offset printing and its impact on the surrounding environment. A qualitative research method was used with a case study approach in several small- and medium-scale offset printing businesses. Data were collected through in-depth interviews, direct observations, and field documentation. The results showed that most printing industry practitioners did not have waste management systems that comply with environmental standards. Liquid and solid wastes containing hazardous chemicals such as solvents, ink, and fixers were still being disposed of without adequate neutralization processes. The environmental impacts included groundwater contamination, pungent odors around business sites, and potential health risks to nearby communities. This study recommends the need for technical training in waste management, active government involvement in supervision, and the adoption of environmentally friendly technologies in the printing process. Therefore, the printing industry is expected to contribute to environmental sustainability without compromising production efficiency.